Health and Nutritional Status of the Hill Korwa Community: A Study of Their Present Situation - Dushyant Kumar Patel,; Dr Esha Chatterjee, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The villages of Hill Korwas are located in the remote hilly areas which is usually cut off from the basic amenities that government and non government levels are offered which include the Anganwadi, Primary Health Centre and Food supply outlets. Such a condition forces them to rely upon the ancient and ancestral medical practices that they have inherited and learnt from their forefathers and few home remedies created by them. Many times they take the medical aid from private practitioners who are usually in the habit of doing malpractices in health and medication in the rural remote areas which is less accessible to the learned population. The villages are cut from the Anganwadi, PDS and Health centres and during monsoons the condition becomes worse.